Colombian entrepreneurial dynamics 2013 (2014)
CONTENIDO: Introducción -- GEM Caribbean -- GEM Model -- Research design --Main results -- Colombian entrepreneurs profile -- Enterprises characteristics -- Special topics -- Entrepreneurial framework conditions